Functional beverage formulation of faloak (Sterculia quadrifida R.Br) stem bark kombucha with the addition of lontar palm sugar - Lalong, Paulus Risan F; Naben, Maria Novalina; Laynurak, Yoseph M (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Local potential and alternative substrates have been widely utilized to make kombucha with the aim of increasing its compound content and potential functional properties. In general, kombucha is made of black or green tea fermented using white cane sugar. On the other hand, the making of kombucha using faloak (Sterculia quadrifida R.Br) stem bark fermented using lontar palm sugar is relatively new. Therefore, the development of the optimum formula needs to be explored to confirm its functional properties. This study aims to determine the optimum formulation of lontar palm sugar concentration and fermentation time in terms of the chemical characteristics and antioxidant activity of faloak stem bark kombucha. The Response Surface Methodology (RSM) was employed in this study with two research factors, i.e., lontar palm sugar concentration and fermentation time. The results reveal the optimum formulation of palm sugar concentration of 15% and fermentation time of 15.18 days which can cause significant changes in properties, showing pH value of 2.72, total acid of 1.264%, total sugar of 6.451%, total phenol of 452.783 mg GAE/L, and antioxidant activity (IC50 value) of 70.877 ppm. In conclusion, the use of 15% lontar palm sugar fermented for 15.18 days can produce faloak stem bark kombucha with potential as a functional beverage.